PEMILIHAN SUMBER PENDANAAN DALAM STUDI KELAYAKAN PENAMBAHAN INVESTASI PADA PT BALI TOWERINDO SENTRA TBK - Darmayanti, Ni Komang; Anom Purbawangsa, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024DO - 10.24843/EEB.2024.v13.i05.p16, 2024)
Investment is an asset financing activity with a payback period of more than one year. Investments in fixed assets are made to meet consumer needs and increase company income. The assessment of the feasibility of investing in PT Bali Towerindo Sentra Tbk is carried out using the ARR, IRR, PP, NPV, and PI methods, certainly the right funding source is also needed so that company can obtain maximum profit so that in this study it will determined using an analysis of profitability between two funding alternatives. This study aims to determine whether a proper investment in fixed assets can increase profits and which source of funding is appropriate to fund the investment so that the company can get a bigger profit. The results of the investment feasibility study using the capital budgeting method show that the investment is feasible, a proper investment can increase profits for the company which can be seen from the EAT estimate after the addition of towers, as well as the analysis of the selection of funding sources shows that the company is better to use funding sources from retained earning and investment credit, this is because the results calculation of RE are greater than the interest of loans, and the results calculation of the RMS is the combined funding sources from investment credit and retained earning are greater than the RMS of funding sources that comes from fully retained earnings.